2014
DOI: 10.1186/1479-5876-12-132
|View full text |Cite
|
Sign up to set email alerts
|

Azithromycin is able to control Toxoplasma gondii infection in human villous explants

Abstract: BackgroundAlthough Toxoplasma gondii infection is normally asymptomatic, severe cases of toxoplasmosis may occur in immunosuppressed patients or congenitally infected newborns. When a fetal infection is established, the recommended treatment is a combination of pyrimethamine, sulfadiazine and folinic acid (PSA). The aim of the present study was to evaluate the efficacy of azithromycin to control T. gondii infection in human villous explants.MethodsCultures of third trimester human villous explants were infecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 52 publications
1
44
0
12
Order By: Relevance
“…In this context, our group showed that azithromycin treatment reduced the vertical transmission of T. gondii tachyzoites in pregnant Calomys callosus rodents and was able to control parasite infection in human trophoblastic cells (BeWo cells) 28,29 . Moreover, we demonstrated that azithromycin treatment promoted inhibition of proliferation of T. gondii Brazilian strains in human villous explants from the third trimester of pregnancy 30,31 . Also, our work with other compounds showed that both enrofloxacin and toltrazuril impairs T. gondii infection in vitro, ex vivo, and in vivo experimental models 32,33 .…”
mentioning
confidence: 84%
“…In this context, our group showed that azithromycin treatment reduced the vertical transmission of T. gondii tachyzoites in pregnant Calomys callosus rodents and was able to control parasite infection in human trophoblastic cells (BeWo cells) 28,29 . Moreover, we demonstrated that azithromycin treatment promoted inhibition of proliferation of T. gondii Brazilian strains in human villous explants from the third trimester of pregnancy 30,31 . Also, our work with other compounds showed that both enrofloxacin and toltrazuril impairs T. gondii infection in vitro, ex vivo, and in vivo experimental models 32,33 .…”
mentioning
confidence: 84%
“…Sections with 4 μm were placed on glass slides and subjected to immunohistochemical analysis (de Oliveira Gomes et al, 2011; Castro-Filice et al, 2014). Briefly, for antigenic retrieval, sections were covered with citric acid pH 6.0 for 5 min in a microwave.…”
Section: Methodsmentioning
confidence: 99%
“…In several mono-infection studies, it has been established that T. gondii and Plasmodium parasites utilise similar cellular mechanisms and biochemical pathways for their nutrition, metabolism, pathology and immunomodulation [ 131 , 132 ]⁠. This might indicate that during co-infections the parasites will result in competitive establishment that may promote or hamper parasite pathogenicity, and foetal and birth outcomes during pregnancy [ 133 ]⁠, severity of anaemia and mortality [ 124 , 134 136 ], and severity of neurological and cerebral involvement [ 137 , 138 , 98 ]. Malaria and Toxoplasma parasites sequester in the placenta resulting in placental disc plate damage thus influencing foetal and pregnancy outcomes [ 139 ].…”
Section: Resultsmentioning
confidence: 99%